Care cascade of hypertension across stages among older adults in India - Umakanta Sahoo; Suraj Maiti; Sanjay K. Mohanty (PLoS ONE, 2025)
Hypertension is now a common disease and the single largest risk factor for premature mortality in India. Hypertensive individuals are not homogenous and have varying risks to life. Although the number of studies on the care cascade of hypertension in India is increasing, no attempts have been made to estimate the prevalence and cascade of care across different stages of hypertension. This study estimates the prevalence, awareness, and treatment of hypertension by stages of hypertension among older adults in India. We analyzed data on 58,787 adults aged 45 years and above from the Longitudinal Ageing Study in India (LASI), Wave 1 (2017−18). Hypertension stages were categorized in accordance with the classification given by the Ministry of Health and Family Welfare, Government of India, and regrouped as per global classification. The age-sex adjusted prevalence, awareness, and treatment rates for different stages of hypertension were estimated. Multinomial logistic regression and the Erreygers’ Concentration Index were used to assess socioeconomic inequalities in hypertension care. We estimated the prevalence of pre-hypertension at 39.9%, stage 1 hypertension at 22.1% and stage 2 hypertension at 9.9%. Increasing age and body mass index were associated with a higher chance of hypertension, whereas living with spouses and children meant having lower odds of hypertension across all stages. The economic condition of the household, educational attainment, and social groups were not significant predictors of hypertension across the stages. The awareness and treatment of hypertension were low across all the stages. The Erreygers’ Concentration Index on awareness and treatment was pro-rich across all the stages of hypertension. A large proportion of hypertensive patients at the advanced stage remain undiagnosed and untreated and carry a higher risk of premature mortality. The awareness and treatment of hypertension are lower among the poorer and socially disadvantaged populations than their richer and more privileged counterparts across all stages.